Impact of improved production technology and mechanized decortication of groundnut (Arachis hypogaea L.) on productivity and income of farmers in Ramanagara district of Karnataka: IMPACT OF IMPROVED PRODUCTION TECHNOLOGY OF GROUNDNUT IN KARNATAKA - S KAMALA BAI; SYED MAZHAR ALI; G KESHAVAREDDY; K H NAGARAJ; LATHA R KULKARNI; S C RANGANATHA (Journal of Oilseeds Research, 2019)
The major production constraints in groundnut cultivation in Ramanagara district, Karnataka are low seed replacement, growing old varieties with less productivity and high susceptibility to leafspots and tikka diseases, lack of awareness on the use of micronutrients and manual decortication leading to drudgery of farm woman. Krishi Vignana Kendra, Ramanagara has conducted FLDs to show the productivity potential and profitability of improved technologies of groundnut and mechanical shelling in farmers' fields. The results revealed that the mean yield increased by 29.1 per cent over farmers' practice in FLD plots. Mechanized power operated shelling decorticator, shelled 62.5 kg/h, at an efficiency of 90.9 per cent. The efficiency was 50 per cent higher than manually peeling, which made the groundnut shelling faster and more thorough in manual operated shelling decorticator. Exclusive shelling performance of power andmanual operated decorticator was evaluated. Power operated sheller was efficient than manual operated sheller recording higher shelling efficiency of 77 per cent and less mechanical damage 1.1 percent over manual operated sheller which recorded 66 and 2.9 per cent, respectively.